Chinese higher education evaluation: theoretical analysis and method construction—Based on CIPP theory - Huang, Yi; Deng, Zhiying (Frontiers in Education, 2026)
Exploring various evaluation methods and distinguishing their applicability can help to find and explore alternative evaluation methods. Chinese higher education has its own characteristics and development laws, so higher education evaluation also has its own particularity. The theoretical paradigm of Chinese higher education evaluation should be explored, which should be rooted in the educational laws and concrete practice situations of China. Based on context, input, process, product (CIPP) educational evaluation theory, this paper analyzes the essence of process evaluation theory and objective evaluation theory firstly. Secondly, this paper compares and analyzes the applicability of general education evaluation theory in China through economic logic, systemic logic, and social reality logic. From the perspective of public welfare, values, evaluation of quality-oriented and social service-oriented, this paper constructs input, process, effectiveness (IPE) education evaluation theory based on socialist values, and the effect orientation of talents and social development evaluation (TSD). Research on CIPP evaluation theory's applicability in Chinese higher education helps to find new evaluation methods suitable for actual situations in different countries and improve the effectiveness of evaluation.